Classic histamine H1 receptors inverse agonists activate ERK1/2 pathway and modulate the transcription of pro-inflammatory genes - Burghi, Valeria (2019)
Recently, we showed that widely used histamine H1 receptor (H1R) ligands that exert therapeutic actions by blocking the effects of histamine (HA), display positive efﬁcacy concerning receptor desensitization and/or internalization. Now we aimed to investigate whether these processes affect the modulation of pro-inflammatory genes and its relationship with the activation of other signaling pathways independent from G protein. While 3 h (long term) exposure to antihistamines decreased expression of pro-inflammatory genes, when we exposed A549 cells, endogenously expressing H1R to HA, chlorpheniramine (CHLOR) or diphenhydramine (DIPH) for 10 min and ligands were removed, ciclooxigenase 2 (COX-2) and interleukin 8 (IL-8) mRNA levels were increased after 2 h 50 min (among 40 and 100% for all ligands, P<0.05). Consistently, ERK1/2 phosphorylation levels were increased by HA (373±102%), CHLOR (95±30%) and DIPH (56±16%), P<0.05, indicating that they display positive efﬁcacy towards this signaling pathway, that has been described to be involved in regulation of both genes. When A549 cells were pre-exposed for 3 h with these ligands, and after 1 h recovery, were stimulated with HA for 10 min, we found lower COX-2 mRNA levels compared to those observed without pretreatment (HA 29.5±0.5%, CHLOR 40.5±16.5 and DIPH 34±8.8% of reduction, P<0.05). We also found lower IL-8 mRNA levels in CHLOR and DIPH pretreated samples (both around 20% of reduction, P<0.05) although no differences were observed in HA pretreated cells. Thus, although short term exposure to antihistamines increase pro-inflammatory genes expression, a prolonged exposure with these ligands diminished it and impaired the increase induced by HA indicating that their anti-inflammatory effects continue despite the ligands being removed. In all, these findings reinforce the biased nature of these ligands and claim for a correct classification, providing evidence for a more rational and safe use of antihistamines.